2004
DOI: 10.1021/jp036403d
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Equilibration Kinetics in Membrane-Bound Photosynthetic Reaction Centers:  Nonlinear Dynamic Effects in Multiple Scattering Media

Abstract: Nonequilibrium dynamic effects in membrane-bound reaction centers (RCs) from photosynthetic bacteria are studied for the first time. We show that the accumulation of slow conformational changes triggered by chargeseparation events in the RCs control system dynamics and depend on illumination conditions in a way similar to that for isolated RCs. The light-induced, transient kinetics of membrane-bound RCs are described using a model of electron-conformational transitions governed by system diffusion along the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
2
11
0
1
Order By: Relevance
“…Furthermore the release of the semiquinone or the electron leak should be postulated only for the case of PG, PS and PI and not for PC, which appears poorly probable. We will than consider LLCS state an open, slow recovering conformation of the RCs in agreement with what suggested in literature (van Mourik et al 2001;Goushcha et al 2000Goushcha et al , 2003Goushcha et al , 2004.…”
Section: Recent Reports Have Described a Llcs State Insupporting
confidence: 78%
See 2 more Smart Citations
“…Furthermore the release of the semiquinone or the electron leak should be postulated only for the case of PG, PS and PI and not for PC, which appears poorly probable. We will than consider LLCS state an open, slow recovering conformation of the RCs in agreement with what suggested in literature (van Mourik et al 2001;Goushcha et al 2000Goushcha et al , 2003Goushcha et al , 2004.…”
Section: Recent Reports Have Described a Llcs State Insupporting
confidence: 78%
“…A possible denaturation of the protein was ruled out observing a complete restoring of the unbleached spectrum upon ferrocene addition. Goushcha et al 2003) and weak (Goushcha et al 2004) illumination conditions. Previous report of slow reactions involving illuminated RCs were also published by Maroti et al (Ka´lma´n and Maro´ti 1997) or Van Der Rest and Gingras (1974).…”
Section: Lipidmentioning
confidence: 99%
See 1 more Smart Citation
“…Both methods apply directly to isolated RCs samples, yet Method 2 can be used in situations where Method 1 may be more difficult to apply. The above descriptions can be applied, with some precautions, to membrane-bound RCs samples, in which multiple scattering effects occur (Goushcha et al 2004). We will use Method 2 to make an approximate estimation of the excitation parameters for membrane samples.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have shown that primary-donor dark recovery kinetics, upon cessation of continuous wave (CW) photoexcitation, depends strongly upon the photoexcitation intensity and duration (Goushcha et al 2003; Goushcha et al 2004). In the analysis of experimental results of RC equilibration kinetics during various illumination conditions, it has been necessary to relate the experimentally measured values of light intensity I exp with corresponding theoretical values I , the frequency of photoexcitation of a single RC per unit time.…”
Section: Introductionmentioning
confidence: 99%